A revision of Prespelea Park (Staphylinidae, Pselaphinae) - Caterino, Michael S. (Zookeys, 2017)
Abstract. We revise the genus Prespelea Park, redefining and redescribing the two previously known species, P. copelandi Park and P. quirsfeldi Park, and adding ten new species: P. parki Caterino & Vásquez-Vélez, sp. n., P. minima Caterino & Vásquez-Vélez, sp. n., P. morsei Caterino & Vásquez-Vélez, sp. n., P. divergens Caterino & Vásquez-Vélez, sp. n., P. carltoni Caterino & Vásquez-Vélez, sp. n., P. myersae Caterino & Vásquez-Vélez, sp. n., P. georgiensis Caterino & Vásquez-Vélez, sp. n., P. enigma Caterino & Vásquez-Vélez, sp. n., P. wagneri Caterino & Vásquez-Vélez, sp. n., and P. basalis Caterino & Vásquez-Vélez, sp. n.. The genus is still only known from a relatively small area in the southern Appalachian Mountains, but the diversity is much greater than previously suspected. The new species exhibit considerable diversity in male secondary sexual characters. A preliminary phylogenetic analysis cannot conclusively resolve the polarity of eye and wing reduction across Speleobamini, but the monophyly of Park’s subgenus Fusjugama, if expanded to include all species with full-eyed and winged males, is not supported, and we therefore synonymize it with Prespelea s. str.